2018
DOI: 10.1016/j.cmi.2018.02.006
|View full text |Cite
|
Sign up to set email alerts
|

Bejel in Cuba: molecular identification of Treponema pallidum subsp. endemicum in patients diagnosed with venereal syphilis

Abstract: Molecular identification of Treponema pallidum subsp. endemicum, the agent of bejel, in Cuban patients diagnosed with syphilis indicates the clear limitations of a diagnosis based exclusively on serology, geographical occurrence, clinical symptoms and anamnestic data. This finding has important implications for Global Public Health Systems, including paradigm changes regarding the location of endemic outbreaks, clinical aspects and transmission of this neglected disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
43
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(46 citation statements)
references
References 24 publications
(24 reference statements)
3
43
0
Order By: Relevance
“…T. pallidum subsp. endemicum can be transmitted via sexual contact (37). Further studies are needed to clarify whether T. pallidum subsp.…”
Section: Discussionmentioning
confidence: 99%
“…T. pallidum subsp. endemicum can be transmitted via sexual contact (37). Further studies are needed to clarify whether T. pallidum subsp.…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that in very dry areas, yaws and bejel symptoms are highly overlapping [43]. The clinical manifestation of TPA and TEN infections is also highly similar, and recent reports have described bejel treponemes in patients suspected of having syphilis in France, Cuba, and Japan [9][10][11][12]. Despite the relatedness of the TPA, TPE, and TEN treponemes, strains belonging to different subspecies cluster together, and this clustering corresponds to disease classification.…”
Section: Plos Onementioning
confidence: 99%
“…Several imported cases of yaws and bejel in children and adults in Europe and North America have been described [7][8][9][10]. In addition, recent studies by Noda et al [11] and Kawahata et al [12] have identified TEN in clinical samples from Cuban and Japanese patients, respectively, who had previously been diagnosed with syphilis.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…More recently, reports of clinically diagnosed genital primary chancres, sexually transmitted and presumed to be syphilis, were shown to have been caused by T. pallidum subsp. endemicum (Grange et al, ; Kawahata et al, ; Mikalova et al, ; Noda et al, ). Thus, “molecular subspeciation” does not always correlate with the clinical manifestations or mode of transmission.…”
Section: Epidemiological and Genetic Researchmentioning
confidence: 99%